The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10692-013-9466-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moisture Content on Strength Characteristics of Non-Uniform Sewing Threads

Abstract: 677.494.022.6: 687.03 and R. A. MakarovaWe consider the effect of moisture content on strength characteristics of composite sewing threads which are used for fabrication of technical textile articles. The proposed structure of the non-uniform sewing threads and the study results showed the effect of moisture on the strength of the threads. We established that even after prolonged exposure to water and temperature, the strength of the threads is sufficient for use of the finished articles.In the Spinning Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore, the alkali resistance of sewing thread had an important impact on the service life of high-temperature dust removal bags. 25 There have been many studies that have focused on the effects of internal factors, [26][27][28][29] such as twist, twist direction, 27 linear density and rheological characteristics, on the performance of sewing threads, 29 and the influence of external factors, [30][31][32][33][34][35] such as sewing speed, temperature, humidity, acid and alkali solution, on its service performance. Tang et al 25 studied the influence of alkali solution on the mechanical properties of Nomex, polytetrafluoroethylene (PTFE) and E-glass fiber sewing threads to simulate the impact of corrosive gas and dust in high-temperature flue gas on sewing thread strength.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the alkali resistance of sewing thread had an important impact on the service life of high-temperature dust removal bags. 25 There have been many studies that have focused on the effects of internal factors, [26][27][28][29] such as twist, twist direction, 27 linear density and rheological characteristics, on the performance of sewing threads, 29 and the influence of external factors, [30][31][32][33][34][35] such as sewing speed, temperature, humidity, acid and alkali solution, on its service performance. Tang et al 25 studied the influence of alkali solution on the mechanical properties of Nomex, polytetrafluoroethylene (PTFE) and E-glass fiber sewing threads to simulate the impact of corrosive gas and dust in high-temperature flue gas on sewing thread strength.…”
mentioning
confidence: 99%
“…Tang et al 25 studied the influence of alkali solution on the mechanical properties of Nomex, polytetrafluoroethylene (PTFE) and E-glass fiber sewing threads to simulate the impact of corrosive gas and dust in high-temperature flue gas on sewing thread strength. Rodionov et al 34 studied the influence of moisture and temperature on properties of the composite sewing thread with identification codes 120 KShN KR-KA and 120 KShN KR-PrA. It was concluded that the composite sewing threads were strong enough to meet the needs of the finished product even if it was exposed to water or high temperature for a long time.…”
mentioning
confidence: 99%
See 2 more Smart Citations